Análisis Jurídico en la Precarización Laboral de las Compañías que Comercializan Cosméticos a través de Venta Directa, en la Provincia de Loja, año 2021 - Namicela Roa, Diana Alexandra (2024)
The present legal research work called Legal Analysis in the Labor Precarization of the Companies that Commercialize Cosmetics through Direct Sales, in the Province of Loja, year 2021, had the general objective of conducting a legal and doctrinal study regarding labor precariousness by the companies that commercialize cosmetics through direct sales in the Province of Loja, which was validated by means of literature review, surveys and interviews. Labor precariousness in companies that market cosmetics through direct sales or printed or digital catalog sales is a phenomenon that has been the subject of legal analysis in several countries; this type of company usually hires independent salespeople, also known as distributors or consultants, who sell the company's products directly to consumers without a contract or work dependence. Direct selling is a work modality that has experienced significant growth in recent years in Ecuador; however, despite its growing economic and social importance, direct selling or catalog sales are not specifically contemplated in the Ecuadorian Labor Code; this has generated a series of legal loopholes that have created conflicts for independent sellers, who do not have a clear regulation that protects their labor rights. The objective of this project is to propose a reform to the Ecuadorian Labor Code to incorporate direct selling or catalog sales as a recognized and regulated work modality; this will provide legal security to independent sellers, who must be recognized as commercial agents since they sell cosmetics for different companies; guaranteeing respect for their labor rights and promoting their economic development.